The Role of Surgical Resection as A Salvage Therapy and Immunohistochemical Stain to Confirm Mediastinal Yolk Sac Tumor - Eka Agustina, Dwi Rosa; Pratiwi, Suryanti Dwi; Retnani, Diah Prabawati; Isharanto, Artono; Erawati, Rachma Dini (Universitaas Brawijaya, 2020)
Background: Mediastinal germ cell tumors are uncommon, representing less than 1% of all malignancies. They mostly occur in young men after puberty and have a poor prognosis with over all long term survival rate 42%. Case Report: We reported a case report in Saiful Anwar Malang Hospital, Indonesia, a young man, 26 years old with an anterior mediastinum tumor and VCSS The CT scan of the chest showed an anterosuperior mediastinal mass which compress the superior vena cava. The result from transthoracic FNAB with USG guidance showed an extragonadal germ cell tumor which resemble an Embryonal Carcinoma from mediastinum. The AFP serum level was elevated. Patient underwent a radiotherapy and a surgical debulking. The biopsy showed an Endodermal Sinus Tumor (Yolk Sac). Immunohistochemical stain for cytokeratin was positive in the tumor cells while stain for CD30 was negative. These were confirming the diagnosis of primary mediastinal yolk sac tumor. Patient received a combination chemotherapy for a total 6 cycles.Conclusion: Some procedures like biopsy, tumor marker, immunohistochemical stain, could differentiate the subtype of mediastinal germ cell tumor. The multimodality treatment by combining chemotherapy with surgical therapy or radiotherapy could increase the survival outcome of patients.